2020
DOI: 10.3390/plants9101286
|View full text |Cite
|
Sign up to set email alerts
|

Infestation of Field Dodder (Cuscuta campestris Yunck.) Promotes Changes in Host Dry Weight and Essential Oil Production in Two Aromatic Plants, Peppermint and Chamomile

Abstract: Peppermint (Mentha piperita L.) and chamomile (Chamomilla recutita (L.) Rausch.) are aromatic plants with considerable economic value. These plants and their essential oils are used in medicine, cosmetics, and the food industry. One of the main limiting factors in peppermint and chamomile commercial cultivation is weed competition since weeds are able to decrease both oil amount and biomass yield. The purpose of the present study was to determine the effect of parasitism by field dodder (Cuscuta campestris Yun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 47 publications
0
10
0
2
Order By: Relevance
“…Only the population Cus62, aged 3 years, was found to germinate more than any other population, including those that were only 1 year old, and the host was the medicinal plant Foeniculum vulgare L. rich in essential oils. Sarić-Krsmanović et al [56] noted a negative impact of C. campestris on essential oil yield from fennel seed, as well as oils isolated from peppermint and chamomile leaves and stems [57]. The study did not include determination of the content of C. campestris essential oil, which could have clarified the matter of exchange of secondary metabolites between the parasite and the host as it could indirectly affect the fruiting and viability of this parasitic flowering plant.…”
Section: Discussionmentioning
confidence: 96%
“…Only the population Cus62, aged 3 years, was found to germinate more than any other population, including those that were only 1 year old, and the host was the medicinal plant Foeniculum vulgare L. rich in essential oils. Sarić-Krsmanović et al [56] noted a negative impact of C. campestris on essential oil yield from fennel seed, as well as oils isolated from peppermint and chamomile leaves and stems [57]. The study did not include determination of the content of C. campestris essential oil, which could have clarified the matter of exchange of secondary metabolites between the parasite and the host as it could indirectly affect the fruiting and viability of this parasitic flowering plant.…”
Section: Discussionmentioning
confidence: 96%
“…Inoculation with PGPB shows an increase in overall growth, trichome density, stomatal density and secondary metabolites in M. × piperita ( del Rosario Cappellari et al, 2015 ). Infestation of M. × piperita with the parasitic plant Cuscuta campestris Yunck has been shown to reduce overall growth and biomass, but increased EO yield ( Sarić-Krsmanović et al, 2020 ). Infested M. × piperita showed an increase in the menthone content, with a decrease in menthol and pulegone content, in comparison to non-infested plants.…”
Section: Effects Of Plant Growth Regulators and Environmental Factors...mentioning
confidence: 99%
“…Previous experiments identified the VOCs α -pinene, β -phellandrene, and β -myrcene as the main chemo-attractants produced by the host species (Runyon et al 2006 ). Another recent study reported that Cuscuta parasitisation significantly and differentially altered the production of essential oils in two different aromatic plants, resulting in the significant reduction of several terpenoids, such as sesquiterpenes (Sarić-Krsmanović et al 2020 ). In addition, it has been proposed that tropism towards a host can also be dependent on the perception of light transmitted by green parts of a plant, as per the case of Cuscuta and sugarbeet plants (Benvenuti et al 2005 ).…”
Section: Introductionmentioning
confidence: 99%